Designing a Holistic Professional Development Program for Elementary School English Teachers in Colombia (2007)
ABSTRACT: The design and implementation of a holistic professional development program for elementary school English teachers in Colombia concerns target language improvement and pedagogical reflection. School-based and learner-centered, the program is characteristic of a synthetic, progressive, process-oriented curriculum as teachers’ language and pedagogical needs determined the learning and pedagogical activities for the program. The teachers improved their use of conventional English and became aware of an alternative approach for early foreign language instruction. They reported increased confidence using English and implementing new methodological strategies by getting positive feedback from their learners. Positive changes in teachers’ and students’ attitudes towards English suggest that this holistic approach be used as a viable professional development program for elementary school teachers in Colombia.